About life, death, and the acts of disposition of corpses: reflections from Peruvian law on the case of Adriana Smith in the United States - Santome-Sánchez, Aldo Alesandro (2025)
The paper analyzes the case of Adriana Smith, a pregnant woman who suffered brain death in Georgia, USA, and whose body was kept on life support to preserve the fetus despite her family’s opposition. From the perspective of Peruvian law, it examines the legal definition of death (irreversible cessation of brain activity) and the legal nature of the corpse as a sui generis object, protected by post-mortem rights derived from prior personality. It highlights that, in Peru, the unborn is recognized as a legal subject from conception, with special protection of life, constitutionally and legally acknowledged. Article 10 of the Civil Code allows the use of corpses to prolong human life, requiring that the family be informed but without needing their consent. Thus, preserving pregnancy through the maintenance of bodily functions would be legally valid, although it entails a delicate balance between the dignity of the corpse and the unborn’s right to life. The study concludes that, although the Peruvian legal framework is not perfect, it offers tools to resolve similar cases, encouraging reflection on gaps and possible reforms to harmonize the protection of life, personal autonomy, and post-mortem respect.